Percepción de la comunidad acerca de la gestión turística del cantón Babahoyo - Suarez Arana, Josué Nahun (2023)
The case study focuses on understanding the perception of the local community in Babahoyo, Ecuador, regarding tourism management in their region. It is known that tourism plays a crucial role in the economic and cultural development of communities, making it important to understand how local residents perceive this management, which becomes vital to ensure the success of problem resolution and to meet the objectives through a survey directed at the inhabitants of Babahoyo. This study aims to analyze the community's perception of the tourism management of the Babahoyo canton in terms of understanding the current perception of Babahoyo residents regarding tourism management in terms of participation in tourism, economic and sustainable development, visitor satisfaction, as well as identifying specific areas of tourism management that the community believes need improvement and the recommendations they propose to address these deficiencies. The active participation of the community and a deep understanding of their perspectives are essential and crucial to achieving excellence in tourism management. This study helps gain knowledge about how to contribute to the construction of a sustainable and enriching tourism future for both the residents and visitors of Babahoyo.